Traditional Surabaya food integrated into the discovery learning e-module: Improving critical thinking and motivation - Rindria Rachma Dewi; W. Wisanti; Y. Yuliani (University of Muhammadiyah Malang, 2025)
The development of the 21st century in the Industrial Revolution 4.0 demands quality human resources with communication, collaboration, critical thinking, and creativity skills in supporting the implementation of the Merdeka Curriculum. This study aimed to analyze the effectiveness of e-module discovery learning integrated with Surabaya traditional food in improving students' critical thinking skills and learning motivation. The research participants were 34 students of class X SMA Negeri 3 Surabaya. Somebody assessed the effectiveness of the e-module based on improving critical thinking skills through pretest and post-test results and learning motivation using the ARCS motivation instrument. Critical thinking and motivation data was analyzed using quantitative descriptive methods, including averages, N-Gain, and T-tests. The results showed a significant increase in each indicator of students' critical thinking skills with a value ≥ 3.27 (very good category) and aspects of ARCS motivation with a value ≥ 3.13 (strong to very strong category). The T-test confirmed that the discovery learning e-module effectively improved critical thinking skills and learning motivation. Integrating local wisdom in learning is an innovative approach that supports the implementation